PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT TRI MANDIRI SELARAS CABANG GADING SERPONG KABUPATEN TANGERANG - Yatin Suroso; Ibnu Sina (Journal of Research and Publication Innovation, 2025)
This study aims to determine The Effect of Work Motivation and Career Development towards Employee Performance at PT. Tri Mandiri Selaras Gading Serpong Tangerang Regency Branch partially and simultaneously. The research method used was a quantitative approach. The type of data used was Primary data, namely the distribution of questionnaires. Data collection at the company PT. Tri Mandiri Selaras Gading Serpong Tangerang Regency Branch, with a population of 112 and a sample of 88. Data analysis using descriptive test analysis, Validity Test, Reliability and classical assumption test including normality test, multicollinearity test and heteroscedasticity test, multiple linear regression analysis, determination coefficient analysis, hypothesis test including partial test (t test) and simultaneous test (f test). The results of this study are that there is a significant positive influence and Motivation on employee performance at PT Tri Mandiri Selaras Gading Serpong Tangerang Regency Branch with a t count of 12.805> t table 1.987, and reinforced by a determination coefficient value of 65.6%. Career development has a significant and positive effect on employee performance at PT Tri Mandiri Selaras Gading Serpong Branch with a t-count of 15.137 > t-table 1.987, and reinforced by a determination coefficient of 72.7%. Work motivation and career development have a significant and positive effect on employee performance at PT Tri Mandiri Selaras Gading Serpong Tangerang Regency Branch with a F-count of 130.137 > F-table 3.10, and is reinforced by a determination coefficient of 75.4%.